Stable Metabolic Control but Increased Demand for Professional Support in Children with Type 1 Diabetes in the Past Ten Years in Bern/Switzerland: A Quality Control Study - Michelle J. Dennig; Grit Sommer; Tanja Zingg; Christa E. Flück; Claudia Boettcher (Journal of Diabetes Research)
Introduction. Lower HbA1c targets and increasingly complex diabetes management with substantially increasing costs dominate today’s type 1 diabetes therapy in children and adolescents. Objective. To evaluate metabolic control in children and adolescents with type 1 diabetes and assess associated factors, evaluate determinants for frequency of healthcare contacts, and compare actual with historical data. Method. This cross-sectional observational study collected data on 178 children and adolescents with type 1 diabetes treated at the University Children’s Hospital in Bern. Results. Mean HbA1c was 7.9% (63 mmol/mol), 33.1% (59/178) of children reached the target of HbA1c<7.5% (<59 mmol/mol), and 18.0% (32/178) had an HbA1c value<7.0% (<53 mmol/mol). Compared to historical data, stable HbA1c levels appeared with a doubled proportion of individuals using insulin pumps. Metabolic control was worse with a longer duration of diabetes and younger age at diagnosis but better when parents came from a Western European country. Age at the consultation, use of diabetes technology and native language influenced the number of healthcare contacts. Younger patients, patients using CSII, and patients without an official Swiss language as mother tongue had more consultations with a healthcare professional than older and native language individuals. Conclusion. The metabolic targets in childhood and adolescent type 1 diabetes are still unmet despite a shift towards more technology. Our study documents a higher demand for support and supervision in specific patient groups. An investment to increase healthcare contacts could help combat the increase in total diabetes cost and significantly improve metabolic control.